Contribution to the knowledge of the jewel beetles (Coleoptera: Buprestidae) fauna of Mazandaran province of Iran - H. Barimani Varandi; M.Yu. Kalashian; H. Barari (Кавказский энтомологический бюллетень, 2009)
34 species of jewel-beetles (Coleoptera, Buprestidae) were collected in Mazandaran province of Iran during 2007–2008. Of these 3 species (Anthaxia sponsa Kiesenwetter, 1857, Agrilus derasofasciatus Lacordaire, 1835, Agrilus obscuricollis Kiesenwetter, 1857) are new for Iranian fauna, and 14 species (Acmaeoderella mimonti (Boieldieu, 1865), Acmaeoderella gibbulosa (Ménétriés, 1832), Lamprodila tuerki (Ganglbauer, 1882), Sphenoptera cauta cauta Jakovlev, 1904, Sphenoptera simplex Jakovlev, 1893, Sphenoptera tappesi Marseul, 1865, Anthaxia passerini (Pecchioli, 1837), Anthaxia hungarica sitta (Küster, 1852), Agrilus graminis Kiesenwette, 1857, Agrilus pratensis Ratzeburg, 1837, Agrilus hyperici (Creutzer, 1799), Coraebus elatus (Fabricius, 1787), Trachys minutus (Linnaeus, 1758) and Trachys phlyctaenoides Kolenati, 1846) are new for Mazandaran province